Time-Dependent Wetting Scenarios of a Water Droplet on Surface-Energy-Controlled Microcavity Structures with Functional Nanocoatings - Pendyala, Prashant; Kim, Hong Nam; Ryu, Yong-Sang; Yoon, Eui-Sung (American Chemical Society, 2020)
We report the surface-energy-dependent wetting transition characteristics of an evaporating water droplet on surface-energy-controlled microcavity structures with functional nanocoatings. The droplet wetting scenarios were categorized into four types depending on the synergistic effect of surface energy and pattern size. The silicon (Si) microcavity surfaces (gamma(Si) = 69.8 mJ/m(2)) and the polytetrafluoroethylene (PTFE)-coated microcavity surfaces (gamma(PTFE) = 15.0 mJ/m(2)) displayed stable Wenzel and Cassie wetting states, respectively, irrespective of time. In contrast, diamond-like carbon (DLC)-coated (gamma(DLC) = 55.5 mJ/m(2)) and fluorinated diamond-like carbon (FDLC)-coated (gamma(FDLC) = 36.2 mJ/m(2)) surfaces demonstrated a time-dependent transition of wetting states. In particular, the DLC-coated surface showed random filling of microcavities at the earlier time point, while the FDLC-coated surface displayed directional filling of microcavities at the late stage of drop evaporation. Such dynamic wetting scenarios based on surface energy, in particular, the random and directional wetting transitions related to surface energy of nanocoatings have not been explored previously. Furthermore, the microscopic role of nanocoating in the wetting scenarios was analyzed by monitoring the time-dependent deformation and movement of the air-water interface (AWI) at individual cavities using the fluorescence interference-contrast (FLIC) technique. A coating-dependent depinning mechanism of the AWI was responsible for variable filling of cavities leading to time-dependent wetting scenarios. A capillary wetting model was used to relate this depinning event to the evaporation-induced internal flow within the droplet. Interestingly, FLIC analysis revealed that a hydrophilic nanocoating can induce microscopic hydrophobicity near the cavity edges leading to delayed and variable cavity filling. The surface energy-dependent classification of the wetting scenarios may help the design of novel evaporation-assisted thermodynamic and mass-transfer processes.